2021
DOI: 10.9734/ijtdh/2021/v42i1130494
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Preventive Strategies among Workers in a Tertiary Health Institution in South-east Nigeria

Abstract: Background and Aim: Healthcare workers have the highest risk of exposure to COVID-19 infection due to the nature of their occupation which daily exposes them to infectious agents/people with COVID-19. The study aimed to determine the knowledge of healthcare workers towards COVID-19 infection prevention strategies and factors that affect infection prevention against COVID-19. Materials and Methods: A hospital-based cross-sectional analytical study conducted in a tertiary health institution. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The COVID-19 risk perception in Nigeria was low, even among HCW. [28] The use of surgical masks among the respondents in this study (56.1%) was similar to 54% reported from a Ugandan study, [22] but less than 87% reported from Italy. [29] The use of facemask by HCW is a crucial safety practice because the surgical mask is cheap, easy to manufacture and widely available.…”
Section: Discussionsupporting
confidence: 80%
“…The COVID-19 risk perception in Nigeria was low, even among HCW. [28] The use of surgical masks among the respondents in this study (56.1%) was similar to 54% reported from a Ugandan study, [22] but less than 87% reported from Italy. [29] The use of facemask by HCW is a crucial safety practice because the surgical mask is cheap, easy to manufacture and widely available.…”
Section: Discussionsupporting
confidence: 80%